1983
DOI: 10.1063/1.444935
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic measurements and liquid structure of DMSO–water mixture

Abstract: The ultrasonic absorption of a 30% mole fraction mixture of dimethyl sulfoxide (DMSO) and water was measured at frequencies from 5 to 200 MHz by a pulse echo technique and over the temperature range −80 to 25 °C. At temperatures above −55 °C the observed absorption is greater than the classical value and is due to volume viscosity. To a very good approximation the ratio of the volume viscosity ηv to the shear viscosity ηs is 2/3. Below −55 °C a simultaneously occuring shear and volume relaxation is observed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 18 publications
2
25
0
1
Order By: Relevance
“…Viscosity studies show a maximum in the shear viscosity concentration curve at 30% DMSO, while ultrasonic studies show a maximum of sound velocity absorption at about 30% DMSO at temperatures 0 ~ to 40~ [2]. These observations, together with the negative heat of mixing, have suggested that a strong hydrogen-bonded complex consisting of two water and one DMSO molecule exists [2].Anhydrous solution of p-toluenesulfonic acid in DMSO has shown continuous absorbance for the excess proton (energy bands) caused by symmetrical H-bonds with double minimum potential well in which the proton i040-0400/96/0400-0i 11509.50/0 9 1996 Plenum Publishing Corporation …”
mentioning
confidence: 97%
See 3 more Smart Citations
“…Viscosity studies show a maximum in the shear viscosity concentration curve at 30% DMSO, while ultrasonic studies show a maximum of sound velocity absorption at about 30% DMSO at temperatures 0 ~ to 40~ [2]. These observations, together with the negative heat of mixing, have suggested that a strong hydrogen-bonded complex consisting of two water and one DMSO molecule exists [2].Anhydrous solution of p-toluenesulfonic acid in DMSO has shown continuous absorbance for the excess proton (energy bands) caused by symmetrical H-bonds with double minimum potential well in which the proton i040-0400/96/0400-0i 11509.50/0 9 1996 Plenum Publishing Corporation …”
mentioning
confidence: 97%
“…While the pure liquid DMSO is thought to have a cluster-like structure, upon addition of water, the cluster structure is suggested to gradually break up as the DMSO-water, water-water, and DMSO-DMSO interactions play a significant role [1]. Viscosity studies show a maximum in the shear viscosity concentration curve at 30% DMSO, while ultrasonic studies show a maximum of sound velocity absorption at about 30% DMSO at temperatures 0 ~ to 40~ [2]. These observations, together with the negative heat of mixing, have suggested that a strong hydrogen-bonded complex consisting of two water and one DMSO molecule exists [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It accounts for the fact that in sonic (compressional) waves volume elements are not just subject to shear but also to volume changes. If no relaxations occur at frequencies above the measurement range, η v = 2/3η s is predicted [7].…”
Section: Introductionmentioning
confidence: 99%